Impact of Contract Research Organizations on Pharmaceutical Industries: A Review - Solanki, Neeta; Verma, Jaya; Kumar, Satyender; Seema3; Mundlia, Jyoti; Saini, Rajesh; Saini, Sapna (Applied Drug Research, Clinical Trials and Regulatory Affairs, 2025)
Contract Research Organizations are bodies that offer research and development services on a contract basis to the pharmaceutical, biotechnology, medical device, and other industries. These organizations offer a wide range of services to support the drug discovery, development, and commercialization process. Initially, CROs begin with clinical trial management facilities and assisting sponsors with clinical study design, whereas laboratory CROs provide drug discovery, manufacturing, and bioanalytical services, including site feasibility. Their services mainly cover pharmaceutical and biotechnology industry based work such as drug development, pharmaceutical product development, clinical and preclinical trials, analytical method developments, pharmacovigilance, medical writing, etc. India presents itself as a wonderful platform for CROs attributing to its huge population, varied disease conditions, accessible human resources, large number of hospitals and low treatment cost. In the clinical trial process, CROs are engaged by the sponsor to accomplish a number of duties, taking into account various administrative and technical responsibilities on behalf of the sponsor. The current manuscript highlights the globalization of clinical trials, the concept of CRO, roles and responsibilities, functions of CROs, regulatory infrastructure of CRO, criteria for selection of suitable CRO, Indian CRO market and impact of COVID-19 pandemic on it.
Keywords: sponsor